Alloimmune-induced intragraft lymphoid neogenesis promotes B-cell tolerance breakdown that accelerates chronic rejection. Issue 4 (August 2016) - Sicard, Antoine; Chen, Chien-Chia; Morelon, Emmanuel; Thaunat, Olivier
Abstract : Purpose of review: Antibody-mediated rejection (AMR) has emerged as a leading cause of allograft loss in solid organ transplantation. A better understanding of AMR immunopathology is a prerequisite to improve its management. Recent findings: The prevalent dogma considers that AMR is the consequence of a thymo-dependent B-cell response against donor-specific polymorphic antigens (mainly mismatched human leukocyte antigen molecules). Nevertheless, antibodies directed against nonpolymorphic antigens expressed by the graft are also generated during chronic rejection and can contribute to allograft destruction. This implies that a breakdown of self-tolerance occurs during chronic rejection. Accumulating evidence suggests that this event occurs inside the ectopic 'tertiary' lymphoid tissue that develops within rejected allografts. Thus, AMR should be viewed as a complex interplay between allo- and autoimmune humoral responses. Summary: The interplay between allo- and autoimmune humoral responses in chronic rejection highlights several unmet medical issues like better diagnosis tools are needed to screen recipients for nonhuman leukocyte antigen alloantibodies and autoantibodies, therapeutic strategies shall aim at blocking the response against alloantigens but also the breakdown of self-tolerance that occurs within tertiary lymphoid tissue.